2023
DOI: 10.3390/polym15040971
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Fe3O4@PEG Nanoparticles Loaded Sorafenib; Molecular Studies and Evaluation of Cytotoxicity in Liver Cancer Cell Lines

Abstract: Iron oxide nanoparticles are one of the nanocarriers that are suitable for novel drug delivery systems due to low toxicity, biocompatibility, loading capacity, and controlled drug delivery to cancer cells. The purpose of the present study is the synthesis of coated iron oxide nanoparticles for the delivery of sorafenib (SFB) and its effects on cancer cells. In this study, Fe3O4 nanoparticles were synthesized by the co-precipitation method, and then sorafenib was loaded onto PEG@Fe3O4 nanoparticles. FTIR was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The additional conjugation of PEG to the functionalized NPs (Cs-CuO and F-Cs-CuO) showed a further increase in viability in the HEK293 cells, and a moderate change in the viabilities of the HeLa and MCF-7 cells, compared to the unPEGylated nanocomplexes. A recent study reported that adding PEG to their NPs (Fe 3 O 4 ) improved the NP stability and biocompatibility in 3T3 and HepG2 cells, preventing any toxic effects of the NPs due to their interactions with the cells or proteins [ 61 ]. Contrary to this, an earlier study using MgFe 3 O 4 NPs noted that adding PEG increased cytotoxicity in breast cancer cells (SKBR-3).…”
Section: Resultsmentioning
confidence: 99%
“…The additional conjugation of PEG to the functionalized NPs (Cs-CuO and F-Cs-CuO) showed a further increase in viability in the HEK293 cells, and a moderate change in the viabilities of the HeLa and MCF-7 cells, compared to the unPEGylated nanocomplexes. A recent study reported that adding PEG to their NPs (Fe 3 O 4 ) improved the NP stability and biocompatibility in 3T3 and HepG2 cells, preventing any toxic effects of the NPs due to their interactions with the cells or proteins [ 61 ]. Contrary to this, an earlier study using MgFe 3 O 4 NPs noted that adding PEG increased cytotoxicity in breast cancer cells (SKBR-3).…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation can still be observed as the coating of polymer on the GO-Fe3O4 nanocomposite is not uniform. Formation of core/shell particles which the GO-Fe3O4 cores are observable as a black area enclosed by a lighter grey shell were determined in both conjugated nanocomposites [22,23]. This may allow for fine dispersion, high oxidation stability and improved drug loading on the shells.…”
Section: Stemmentioning
confidence: 99%
“…Sorafenib (SFB) inhibits the formation of nucleic acids by connecting to DNA. Simple, PEG-coated magnetite nanoparticles were used for SFB loading and characterized for potential application in liver cancer treatment [75]. The presence of PEG was beneficial for better stability, biocompatibility, lower toxic and pharmacokinetic effects.…”
Section: Treatment Of Other Cancersmentioning
confidence: 99%